Sintesis dan Karakterisasi Membran untuk Proses Ultrafiltrasi - Aprilia, Sri; Amin, Amri (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2011)
Asymmetric ultrafiltration (UF) membranes were prepared from three kinds of polymer namely polyacrilonitryle (PAN), polysufone (PS), and cellulose acetate (CA) by phase inversion method. Water was used as non-solvent. These membranes were charachterized for ultrafiltration membranes i.e measurement of solvent permeability (Lp), Molecular Weight Cut Off membranes (MWCO) with various molecular weight of solute dekstran, and morphology of the membrane by Scanning Electron Microscopy (SEM). SEM analysis includes surface area and cross section area. Membranes with polymer low concentration 10% as PAN-1, PS-1 and CA-1 have the larger Lp from PAN-2, PS-2, and CA-2 that have concentration 15% for the same type of polymer. These occur because of the larger pore membrane than high concentration of polymer. SEM analysis showed a homogeneous distribution in the surface membrane and pore of membran like sponge structure from cross section area. Membranes CA-1, CA-2, FS-1 and FS-2 have Molecular Weight Cut off (MWCO) for the solute dextran 40000 Da. For PS-2 and PS-2 membranes have MWCO of dextran above 20000 Da.Keywords: ultrafiltration membrane, solvent permeability coeficient, MWCO, membrane morphology